Prevalence and quantification of Vibrio species and Vibrio parahaemolyticus in freshwater fish at hypermarket level - Ahmad, Noorlis; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Tuan Chilek, Tuan Zainazor; Ponniah, Jeyaletchumi; Robin, Tunung; Tang, John Yew Huat; Nishibuchi, Mitsuaki; Nakaguchi, Yoshitsugu; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Little is known on the biosafety level of Vibrio spp. in freshwater fish in Malaysia. The purpose of this study was to investigate the prevalence and concentration of Vibrio spp. and V. parahaemolyticus in freshwater fish using the Most Probable Number-Polymerase Chain Reaction (MPN-PCR) method. The study was conducted on 150 samples from two types of freshwater fish commonly sold at hypermarkets, i.e. Pangasius hypophthalmus (catfish) and Oreochromis sp. (red tilapia). Sampling was done on the flesh, intestinal tract and gills of each fish. The prevalence of Vibrio spp. and V. parahaemolyticus was found to be 98.67% and 24% respectively with higher percentages detected in samples from the gills followed by the intestinal tract and flesh. Vibrio spp. was detected in almost all red tilapia and catfish samples. V. parahaemolyticus was detected in 25% of the catfish samples compared to 22.6% of red tilapia fish. The density of Vibrio spp. and V. parahaemolyticus in the samples ranged from 0 to 1.1x107 MPN/g. Although the maximum value was 1.1x107 MPN/g, most samples had microbial loads ranging from 0 to >104 MPN/g. The outcome on the biosafety assessment of Vibrio spp. and V. parahaemolyticus in freshwater fish indicates another potential source of food safety issues to consumers.